Actividad de la Editorial. (UNED, 2023)
Mesa principal, de izquierda a derecha , en la mesa principal René Muiños Gual, Eugenio Rodríguez Vega, Inés Trejos Araya, Rodrigo Arias Camacho, Alberto Cañas Escalante, Luis Guillermo Carpio Malavassi